Naïve Bayes Algorithm Implementation To Predict Gum Production at PT. Sri Rahayu Court: Naïve Bayes Algorithm Implementation To Predict Gum Production at PT. Sri Rahayu Court - Muhammad Ibnu Hawari; Bosker Sinaga (Jurnal Mantik, 2019)
Latex is the production produced from rubber trees by means of tapping using a special knife, and in the plantations there are some plants produce processed in the plant itself becomes a basic ingredient or finished goods to consumers. During this time determine the outcome prediction latex production does not use a method so the results are not in accordance with what diharafkan. This is due to the lack of an objective method to decide the outcome prediction latex production, the rapid selection based on the data of workers tapping some rubber trees with some techniques and ways to get good results. With reference to the solutions provided Naïve Bayes algorithm to help predict the outcome of latex production, A leader collects sap yield of 3 items are Latex, Lump and Treelace. Calculations are done with the third item Naïve Bayes algorithm method with classifications that apply data mining and data probability. Data Mining is generally defined as a system capable of generating and handling of problem solving. Naïve Bayes algorithm can determine the value of the preferences of each alternative, and may be the best alternative from a number of alternatives.